2012
DOI: 10.1007/s00484-012-0606-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma symptoms in schoolchildren, and climate in west European countries: an ecologic study

Abstract: The aim of the present study was to estimate the associations between the prevalence of asthma symptoms in schoolchildren and meteorological variables in west European countries that participated in the International Study of Asthma and Allergies in Children (ISAAC), Phase III 1997-2003. An ecologic study was carried out. The prevalence of asthma was obtained from this study from 48 centers in 14 countries, and meteorological variables from those stations closest to ISAAC centers, together with other socioecon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 73 publications
0
5
1
1
Order By: Relevance
“…In 2010–2011, the age–gender‐corrected admission rate for asthma was 233 admissions per 100 000 children in England. It is unlikely that the observed effect is the result of variation in asthma prevalence alone as it is relatively large and bigger than that previously reported (around 1% for every 100 additional HOS) .…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…In 2010–2011, the age–gender‐corrected admission rate for asthma was 233 admissions per 100 000 children in England. It is unlikely that the observed effect is the result of variation in asthma prevalence alone as it is relatively large and bigger than that previously reported (around 1% for every 100 additional HOS) .…”
Section: Resultscontrasting
confidence: 61%
“…Acute asthma admissions are also subject to considerable seasonal variation with numbers peaking in the United Kingdom between September and December . Long‐term weather patterns have been shown to have a small effect on prevalence of childhood asthma , but the effects of longer‐term weather patterns on hospital use or asthma control have not been studied.…”
mentioning
confidence: 99%
“…In contrast, low humidity was related to worsening asthma and asthma-related hospital admissions in other studies 1816. The prevalence of asthma showed a negative association with relative humidity in western European countries 17. Regarding the effects of wind on asthma, a few studies have reported inconsistent results.…”
Section: Discussionmentioning
confidence: 87%
“…Prevalence of wheezing ever in infants varies across different regions, from 29% in countries in Northern Europe, to 48% in countries in Southern Europe, and 27% in the United States of America (USA) (4). Previous studies have found associations between rainy weather and severe current wheeze in schoolchildren (5), and stronger associations of some risk and protective factors of recurrent wheezing when latitude increases (6).…”
Section: Introductionmentioning
confidence: 99%